A high selective fluorescent sensor for Cu2+ in solution and test paper strips. (February 2020) - Shi, Fu; Cui, Shiqiang; Liu, Hongling; Pu, Shouzhi
Abstract: A novel and efficient fluorescent sensor with a pyrazine triphenylamine unit was developed. The sensor exhibits large Stokes shift (216 nm) due to the excited-state intramolecular proton transfer (ESIPT) process. After complexing with Cu 2+, the ESIPT process was blocked and the fluorescence of the sensor was quenched. Job's plot and ESI-MS results indicated that the stoichiometric ratio between the sensor and Cu 2+ was 1:1. The detection limit was determined to be 2.47 × 10 −8  mol L −1 . The sensor could be used to detect Cu 2+ in practical samples with high accuracy. Furthermore, the sensor also could be made into test paper strips for the qualitative and quantitative detection of Cu 2+ . Graphical abstract: A high selective fluorescent sensor with a pyrazine unit has been synthesized. The sensor not only could be applied to determine Cu 2+ in practical water samples, but also could be made into test paper strips for qualitative and quantitative determination of Cu 2+ . Image 1 Highlights: This paper reports a fluorescent chemosensor with a hexafluorocyclophentene unit and a pyrazine unit for the first time. The sensor could be applied to detect Cu 2+ in practical samples with high accuracy. The sensor also could be made into test paper strips for qualitative and quantitative determination of Cu 2+ .